The role of human mast cells in allergy and asthma. Issue 3 (1st March 2022) - Banafea, Ghalya H; Bakhashab, Sherin; Alshaibi, Huda F; Natesan Pushparaj, Peter; Rasool, Mahmood
ABSTRACT: Mast cells are tissue-inhabiting cells that play an important role in inflammatory diseases of the airway tract. Mast cells arise in the bone marrow as progenitor cells and complete their differentiation in tissues exposed to the external environment, such as the skin and respiratory tract, and are among the first to respond to bacterial and parasitic infections. Mast cells express a variety of receptors that enable them to respond to a wide range of stimulants, including the high-affinity FcεRI receptor. Upon initial contact with an antigen, mast cells are sensitized with IgE to recognize the allergen upon further contact. FcεRI-activated mast cells are known to release histamine and proteases that contribute to asthma symptoms. They release a variety of cytokines and lipid mediators that contribute to immune cell accumulation and tissue remodeling in asthma. Mast cell mediators trigger inflammation and also have a protective effect. This review aims to update the existing knowledge on the mediators released by human FcεRI-activated mast cells, and to unravel their pathological and protective roles in asthma and allergy. In addition, we highlight other diseases that arise from mast cell dysfunction, the therapeutic approaches used to address them, and fill the gaps in our current knowledge. Mast cell mediators not only trigger inflammation but may also have a protective effect. Given the differences between human and animal mast cells, this review focuses on the mediators released by human FcεRI-activated mast cells and the role they play in asthma and allergy. Graphical Abstract: uf0001